1930
DOI: 10.1002/recl.19300490711
|View full text |Cite
|
Sign up to set email alerts
|

Sur L'influence de la Composition et de la Configuration des Acides Gras Insaturés Isomères sur la Vitesse de L'oxydation par L'acide Peracétique

Abstract: C'est en effet le cas. Les derniers se comportent comme des substances avec une liaison double, (qui ne se trouve par sous l'influence dun groupe CO) et l'oxydation des deux liaisons doubles a lieu sans grandes differences de la vitesse, les premiers &ant attaques d'abord tres vivement, tandis que la reaction se ralentit brusquement du moment ou la moitie de l'insaturation a disparue Dam le cas oti nous avons affaire A un systeme de trois liaisons doubles conjuguees un tiers de l'insaturation a disparu apres e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1935
1935
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Several studies have investigated the possible oxidation of organic compounds by PAA and reported that PAA reactivity with respect to organic compounds is very selective. ,, ,, Overall, the oxidation mechanism of organic compounds by PAA is the transfer of a single oxygen atom from PAA to electron-rich sites on the compound. PAA reactivity is highly affected by the electron-withdrawing or electron-donating character of the substituents of organic compounds.…”
Section: Reactivity Of Organic Compounds With Respect To Paamentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the possible oxidation of organic compounds by PAA and reported that PAA reactivity with respect to organic compounds is very selective. ,, ,, Overall, the oxidation mechanism of organic compounds by PAA is the transfer of a single oxygen atom from PAA to electron-rich sites on the compound. PAA reactivity is highly affected by the electron-withdrawing or electron-donating character of the substituents of organic compounds.…”
Section: Reactivity Of Organic Compounds With Respect To Paamentioning
confidence: 99%
“…128 The rate constants for reaction of alkenes with PAA were reported from 3.2 × 10 −6 to 3.7 × 10 −2 M −1 s −1 (Table 2) by four early studies. 46,118,119,126 The reaction rates of PAA with alkenes should be enhanced by an increase in the electron density at the point of attack. Thus, the introduction of neighboring electron-donating groups accelerates the reaction of alkenes with PAA.…”
Section: Reactivity Of Organic Compounds Withmentioning
confidence: 99%